Realisasi Bantuan Alat Mesin Pertanian Kepada Subak (Kasus Pelaksanaan Program Upaya Khusus Peningkatan Produksi Padi Jagung dan Kedelai di Subak Penginyahan Desa Puhu Kecamatan Payangan Kabupaten Gianyar) - PRADNYANA, I NYOMAN USADI; SUARDI, I DEWA PUTU OKA; DJELANTIK, A.A.A WULANDIRA SAWITRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.6, No.4, Oktober 2017, 2017)
The Realization of Agricultural Machinery Aid To Subak (Implementation Case of Special Effort Program Enhancement of Rice Corn and Soybeans Production in Subak Penginyahan, Puhu Village of Payangan District, Gianyar) Indonesia is one of agricultural country and most of the citizen work in agriculture sector but in some recent years Indonesia always import food from other countries, to prevent this from happening continuously in 2015, the government makes a special effort progarm (Upsus) enhancement of rice, corn, and soybeans production in 2017 is expected that Indonesia has reached food self-sufficiency, Upsus program has some kind of aids like agricultural equipment and machine aid (Alsintan) that is expected to simplify and speed up the production process.This study aims to find out (1) To find out the suitability of the proposed agricultural machinery aid (Alsintan) proposed by Subak Penginyahan; (2) To find out the use of agricultural machinery which is Subak Penginyahan recieved.The location of this research is located in Subak Penginyahan, Puhu Village, Payangan District, Gianyar Regency. Population of this research is 70 active members of Subak Penginyahan. Sample size was determined using Nottoadmojo formula, so the number of respondents who were taken 41 people and added with 1 respondent from Agriculture Department of Gianyar Regency, 1 PPL respondent who in charge at Penginyahan Subak and 1 respondent from Pekaseh Subak Penginyahan.The result of this study indicates that the realization of Alsintan aid in Subak Penginyahan is not suitable as purposed. There are differences in numbers and types of Alsintan that is proposed with received by Subak. For Alsintan type received by Subak is alsintan hand tractor type with this the realization of Alsintan aid that is purposed by Subak is suitable with what is proposed by Subak. Based on findings of the research that the writer conducted, it can be suggested to the government to increase its attention to the farmer continuously; In this case to continue aids provision that could help and provoke the enthusiasm of farmers to farm.